Risk-based learning games improve long-term retention of information among school pupils - Devonshire, Ian M.; Davis, Jenny; Fairweather, Sophie; Highfield, Lauren; Thaker, Chandni; Walsh, Ashleigh; Wilson, Rachel; Hathway, Gareth J. (Public Library of Science, 2014)
Risk heightens motivation and, if used appropriately, may have the potential to improve engagement in the classroom. We have developed a risk-based learning game for school pupils in order to test whether such learning games can improve later recall of information. The study was performed during a series of public engagement workshops delivered by undergraduate students. Undergraduate neuroscience students delivered 90-minute science workshops to 9–10 year old school pupils (n = 448) that were divided into ‘Risk’, ‘No risk’ and ‘Control’ classes. ‘Risk’ classes received periodic multiple-choice questions (MCQs) during the workshops which required small teams of pupils to assign tokens to the answer(s) they believed to be correct. Tokens assigned to the correct answer were returned to the group and an equal number given back as a prize; tokens assigned to incorrect answers were lost. Participation was incentivised by the promise of a brain-related prize to the team with the most tokens at the end of the workshop. ‘No risk’ classes received MCQs without the risk component whilst the ‘Control’ classes received no MCQs. When presented with a neuroscience quiz based on workshop content at the end of the workshop, pupils in the ‘Risk’ classes exhibited significantly greater recall of information one week later. Quiz scores were higher than scores from the day of the workshop which suggested pupils may have discussed the workshop content outside of the classroom, thereby increasing knowledge over and above what was learned during the workshop. This is supported by feedback from pupils in ‘Risk’ classes which indicated that ‘Risk’ workshops were more interesting than ‘No risk’ and ‘Control’ workshops. These data suggest that there is a role for risk in the classroom but further -investigations are required to elucidate the causal mechanisms of improved retention of information.